Beitrag zur Effizienzsteigerung mobiler Arbeitsmaschinen: Entwicklung einer elektrohydraulischen Bedarfsstromsteuerung mit aufgeprägtem Volumenstrom - Scherer, Martin (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2015)
The drive line of the working equipment of mobile machines is mainly composed of fluid power systems. Electro-hydraulic components facilitate the development of innovative Flow-on-Demand hydraulics. In these systems the oil flow of the pump is derived from the consumer requests and directly set in an open-loop control. Principle related power dissipation is reduced. Additionally, faster system response improves machine operability and ease of use.